Efficient In‐Cloud Removal of Aerosols by Deep Convection. Issue 2 (23rd January 2019) - Yu, Pengfei; Froyd, Karl D.; Portmann, Robert W.; Toon, Owen B.; Freitas, Saulo R.; Bardeen, Charles G.; Brock, Charles; Fan, Tianyi; Gao, Ru‐Shan; Katich, Joseph M.; Kupc, Agnieszka; Liu, Shang; et al.
Abstract: Convective systems dominate the vertical transport of aerosols and trace gases. The most recent in situ aerosol measurements presented here show that the concentrations of primary aerosols including sea salt and black carbon drop by factors of 10 to 10, 000 from the surface to the upper troposphere. In this study we show that the default convective transport scheme in the National Science Foundation/Department of Energy Community Earth System Model results in a high bias of 10–1, 000 times the measured aerosol mass for black carbon and sea salt in the middle and upper troposphere. A modified transport scheme, which considers aerosol activation from entrained air above the cloud base and aerosol‐cloud interaction associated with convection, dramatically improves model agreement with in situ measurements suggesting that deep convection can efficiently remove primary aerosols. We suggest that models that fail to consider secondary activation may overestimate black carbon's radiative forcing by a factor of 2. Plain Language Summary: Convective systems dominate the vertical transport of aerosols and trace gases. The most recent global aerosol measurements show that the concentrations of primary aerosols including sea salt and black carbon drop by a factor of 10–10, 000 from the surface to the upper troposphere. In this study, we show that a climate model overestimates black carbon and sea salt in the middle and upper troposphere by factors of 10–1, 000 when compared with observations from a number of field campaigns. The default transport scheme in a climate model not only significantly overestimates black carbon and sea salt in the upper troposphere but also overestimates the total aerosol mass budget by a factor of 3 in the global middle and upper troposphere. We modify the convective transport scheme in the climate model by including aerosol activation and removal processes above the cloud base. The new convective transport scheme dramatically improves model performance on the global aerosol budget in the middle and upper troposphere. We show in this study that models fail to consider aerosol secondary activation from the entrained air may overestimate black carbon's radiative forcing by a factor of two. Key Points: Deep convection efficiently removes particles at and above the cloud base The default convective scheme in climate model overestimates middle and upper tropospheric aerosol (sea salt and black carbon) by a factor of 10–1, 000 The default convective transport scheme overestimates black carbon's radiative forcing by a factor of 2